Jovian Vortex Hunter: A Citizen Science Project to Study Jupiter’s Vortices - Ramanakumar Sankar; Shawn Brueshaber; Lucy Fortson; Candice Hansen-Koharcheck; Chris Lintott; Kameswara Mantha; Cooper Nesmith; Glenn S. Orton (The Planetary Science Journal, 2024)
The Jovian atmosphere contains a wide diversity of vortices, which have a large range of sizes, colors, and forms in different dynamical regimes. The formation processes for these vortices are poorly understood, and aside from a few known, long-lived ovals, such as the Great Red Spot and Oval BA, vortex stability and their temporal evolution are currently largely unknown. In this study, we use JunoCam data and a citizen science project on Zooniverse to derive a catalog of vortices, some with repeated observations, from 2018 May to 2021 September, and we analyze their associated properties, such as size, location, and color. We find that different-colored vortices (binned as white, red, brown, and dark) follow vastly different distributions in terms of their sizes and where they are found on the planet. We employ a simplified stability criterion using these vortices as a proxy, to derive a minimum Rossby deformation length for the planet of ∼1800 km. We find that this value of L _d is largely constant throughout the atmosphere and does not have an appreciable meridional gradient.